2023
DOI: 10.4103/injms.injms_5_23
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammation Response Index and Systemic Immune Inflammation Index for Predicting Acute Cholecystitis

Günay Yildiz,
Fatih Selvi,
Cihan Bedel
et al.

Abstract: Objective: Acute cholecystitis (AC) is a condition caused by acute inflammation of gallbladder. Many inflammatory markers are frequently used in the diagnostic process. In this study, we wanted to show the diagnostic efficacy of the systemic inflammatory response index (SIRI) and systemic immune inflammation index (SII) in patients with AC. Methods: This retrospective study was conducted in subjects diagnosed with AC between January 1, 2020, and June 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“… 30 , 31 In the context of cholecystitis, previous studies have revealed that SII levels exhibit a significant elevation in patients with acute cholecystitis compared to healthy individuals. 32 Furthermore, SII can serve as a positive predictor for the severity of acute cholecystitis. 33 It has also demonstrated associations with short-term outcomes and advanced forms of acute cholecystitis.…”
Section: Discussionmentioning
confidence: 99%
“… 30 , 31 In the context of cholecystitis, previous studies have revealed that SII levels exhibit a significant elevation in patients with acute cholecystitis compared to healthy individuals. 32 Furthermore, SII can serve as a positive predictor for the severity of acute cholecystitis. 33 It has also demonstrated associations with short-term outcomes and advanced forms of acute cholecystitis.…”
Section: Discussionmentioning
confidence: 99%